Pengembangan Alat Evaluasi Fisika Untuk Mengidentifikasi Miskonsepsi Siswa Kelas VIII SMP Negeri Oenino - Laurensia Missa; Ruth Novi Kornalia Mellu; Demeryati Langtang (Jurnal Fisika Indonesia, 2020)
The objective of study was developing diagnostic test evaluation instrument in multiple choice form with predetermined reason to identify Grade VIII student’s misconceptions on force topic in SMPN Oenino. Population of the study covered all students whereas the samples were Grade VIII students SMPN Oenino. The research method was Research and Development (R&D) with potential and problem, gathering information, product design, product validation, product revision, and product trial. Validation phase included experts and content validation. On expert’s validation, test instrument was validated by 3 validators with 87,7% worthiness average and was recommended applicable without revision. On content validation, 45 test items were tried out to students and 17 items were declared valid ranging from C1 to C4 cognitive domain which were used later to identify student’s misconceptions. Their misconceptions on force material were 23%, 38%, 13% and 26% from C1 to C4 cognitive domains. The result indicated that this instrument was applicable to identify student’s misconception on force materials.